The analysis of impact of metaverse on the Fintech industry based on text mining and association rules mining - Hui Liu; Miseon Choi; Jinhwa Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of our study is to explore the influence of Metaverse on FinTech industry and identify the mediators between them. Design/methodology/approach: To achieve the purpose, we conducted words frequency analysis, network analysis, and association rules analysis, based on 68,957 Metaverse-related and 23,902 FinTech-related news articles from January 1, 2021, to September 31, 2023. Findings: The results from the analysis indicate that the five most frequently shown words are 'Metaverse', 'Fintech', 'Technology', 'Investment', and 'Platform'. Additionally, the outcomes of association rules analysis highlight relationships between the Metaverse and FinTech through terms like 'Service', 'Platform', 'Digital' and 'Information'. Research limitations/implications: Our findings emphasize the crucial significance of Metaverse in FinTech Industry, providing insights for related investors or stakeholders. The reliance on news data only may have constrained the depth of insights ion the dynamics between the Metaverse and FinTech, thereby future study could benefit from video content, industry reports or white papers. Originality/value: While many studies on the Metaverse and FinTech focus on exploratory or theoretical discussions, this study performed an in-depth textual analysis of the collected text data on these topics. This study not only provides understanding of the relationship between the Metaverse and FinTech but also suggests future applications in other fields.
Keywords: 650; Metaverse; Fintech industry; Text mining; Association rules mining